A two-stage dissolved air flotation saturator configuration for significant microbubble improvement. Issue 9 (16th April 2023) - Nikfar, Mohamad Hosein; Parsaeian, Hesam; Amani Tehrani, Ali; Kouhestani, Alireza; Masoumi Isfahani, Hamidreza; Bazargan, Alireza
ABSTRACT: The presence of suspended contaminants in water and wastewater, such as algae, colloids, fats and oil, necessitates the use of systems such as dissolved air flotation (DAF) for their removal. In the current study, a novel setup has been proposed for bubble enhancement. An industrial scale (pilot) DAF system was tested at saturator pressures of 3–7 atm and flow rates of 5–20 L/min in three different configurations, namely, empty, packed, and the innovative two-stage (TS) configuration. In the TS system, after the nucleation of micro bubbles, the water is returned to the saturator to undergo pressurization for a second time before it is passed through the nozzle once more and is released. The results show that the highest volume of released air as well as the smallest microbubbles are seen in the TS configuration, followed by packed mode, with the empty configuration showing the least favourable results. Moreover, the bubbles produced at the lowest residence time and pressure (3 atm) with the novel setup are better than the bubbles produced by the standard configuration, even with pressures as high as 7 atm. Thus, the novel TS setup can allow for significantly lower energy requirements and lower capital costs. For real-world application of the TS system, the feed for the saturator could be extracted from within or near the contact zone, i.e. where the bubbles are released in the DAF tank. GRAPHICAL ABSTRACT: UF0001